Ram Ke Nam - Patwardhan, Anand (India : Patwardhan, Anand, 1991)
This film follows the campaign by the militant movement Vishva Hindu Parishad (VHP) to destroy a 16th century mosque in the city of Ayodhya. Supporters of the VHP claim that the mosque stands right on the birthplace of the Hindu god Ram, and that in order to build it the temple to Ram was destroyed several centuries ago. In retaliation they now demand the destruction of the Muslim sanctuary and the building of a new temple to honor the god Ram. The conflict escalated into open violence, in which thousands of people lost their lives. The film is a powerful testimony about how far religious intolerance can lead.
Duration: 01:15:00
Keywords: Documentary films